2018
DOI: 10.1177/1049909118792179
|View full text |Cite
|
Sign up to set email alerts
|

Upper Extremity Subcutaneous Lymphatic Drainage “Lymphocentesis” for Symptom Relief in End-Stage Breast Cancer

Abstract: Lymphedema is a challenging condition that occurs as a complication to many life-limiting medical conditions. It has a number of associated symptoms including pain, functional impairments, and emotional distress. Majority of treatment interventions have been studied and applied outside of the palliative care context. Subcutaneous drainage is a technique that has been used in some case reports for the lower extremity and sacrum with good results. This report describes an adapted technique of subcutaneous draina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…It is essential to have a clear information, with education, risk prevention strategies, clear goals to achieve, an adequate risk/benefit balance, early diagnosis and intervention, and an emphasis on quality of life over the complete resolution of lymphedema. All this have been showed to improve adhesion and outcomes [10,12]. Our patient received pharmacological strategies with steroids and diuretics with poor response, foreseen by the anatomical involvement generating by the large tumor volume that involved intraabdominal vascular structures such as compression of the vena cava.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It is essential to have a clear information, with education, risk prevention strategies, clear goals to achieve, an adequate risk/benefit balance, early diagnosis and intervention, and an emphasis on quality of life over the complete resolution of lymphedema. All this have been showed to improve adhesion and outcomes [10,12]. Our patient received pharmacological strategies with steroids and diuretics with poor response, foreseen by the anatomical involvement generating by the large tumor volume that involved intraabdominal vascular structures such as compression of the vena cava.…”
Section: Discussionmentioning
confidence: 91%
“…Several case reports of the use of subcutaneous drainage for management of chronic lower limb lymphedema have shown benefit in fragile patients with advanced diseases, especially those refractories to conventional measures [2,5,8,9]. Liao et al [12] reported the therapy of controlled subcutaneous drainage in upper limb lymphedema refractory to decongestant therapy with adequate response in control of the symptoms and functionality [12].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are aligned with the existing evidence on the use, feasibility, efficacy and safety of S.C controlled drainage of edema in the palliative care setting for the relief of physical suffering and quality of life improvement. 1 -9…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous drainage is a well-known technique for the treatment of edema of both lower and upper extremities and anasarca due to advanced medical conditions such deep vein thrombosis, hypoalbuminemia, heart failure, advanced cancer obstruction of lymphatic collectors and severe renal failure. 5 -9 Especially because of the organized nature of the lymphedema and patients´ mobility limitation restricted by the weight of the edematous limb, the benefit of drug interventions and mechanical treatments are limited. The literature shows that S.C. controlled drainage is a technically simple procedure, with an effective decrease of limb edema, and lack of tissue infectious and inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%